DEFINING FEEDER VESSEL’S EFFICIENT ROUTE DISTANCE TO MAKE THE SUPPLY CHAIN EFFICIENT AND REDUCE THE ENVIRONMENTAL CATASTROPHE ACCORDING TO MARPOL AND LOCAL REGULATIONS - MAJUMDAR, SUNANDA; BAPPY, KHALID MAHMUD (Journal of Maritime Logistics, 2022)
Feeder vessels are the necessary part of the transport system that mother vessels can’t reach. In contrast, the frequent transmittable feeder vessels can affect the environment drastically and shift the factors of environmental catastrophe entirely. This shift can be stopped with reasonable restrictions in light of MARPOL and other regulations. Through data-driven strategy and state legislation, laws regarding the movement of the feeder vessels and other factors can be controlled and bought to a minimum. Proper strategy execution is also a major part of making an efficient route system and reducing the Hydrometeorological environmental catastrophe.